Developing criteria for evaluation of geroprotectors as a key stage toward translation to the clinic. Issue 3 (11th March 2016) - Moskalev, Alexey; Chernyagina, Elizaveta; Tsvetkov, Vasily; Fedintsev, Alexander; Shaposhnikov, Mikhail; Krut'ko, Vyacheslav; Zhavoronkov, Alex; Kennedy, Brian K.
Summary: In the coming decades, a massive shift in the aging segment of the population will have major social and economic consequences around the world. One way to offset this increase is to expedite the development of geroprotectors, substances that slow aging, repair age‐associated damage and extend healthy lifespan, or healthspan. While over 200 geroprotectors are now reported in model organisms and some are in human use for specific disease indications, the path toward determining whether they affect aging in humans remains obscure. Translation to the clinic is hampered by multiple issues including absence of a common set of criteria to define, select, and classify these substances, given the complexity of the aging process and their enormous diversity in mechanism of action. Translational research efforts would benefit from the formation of a scientific consensus on the following: the definition of 'geroprotector', the selection criteria for geroprotectors, a comprehensive classification system, and an analytical model. Here, we review current approaches to selection and put forth our own suggested selection criteria. Standardizing selection of geroprotectors will streamline discovery and analysis of new candidates, saving time and cost involved in translation to clinic.